The Competencies, Roles and Scope of Practice of Advanced Psychiatric Nursing in Indonesia - Wardani, Yulia (Nurse Media Journal of Nursing, 2013)
The graduate advanced psychiatric nursing (psychiatric nursing specialist) from master degree in Indonesia are about 70 nurses, 67 nurses were graduated from University of Indonesia. They are working at mental health services and educational setting around Indonesia and yet seem not ready to perform some specific advanced competencies in clinical area. The mastery on mental health assessment, neurochemical perspectives, medical management and psychotherapy have not yet performed by the psychiatric nurse specialist in the clinical area or community.To have those competencies and its performances, therefore the curriculum in a psychiatric nursing graduate program must include advanced courses in physiopsychology, psychopathology, advanced psychopharmacology, neurobehavioral science, advanced mental health assessment, and advanced treatment interventions such as psychotherapy and prescription and management of psychotropic medications as their core and major courses in the curriculum. Those courses should be performed in their clinical practice courses or other related learning experiences. When those qualifications are met, then they are competent to be called advanced psychiatric nurse.As advanced practice registered nurses, the advanced psychiatric nurses should be able to demonstrate their direct expertise and roles in advanced mental health assessment, diagnostic evaluation, psychopharmacology management, psychotherapy with individuals, group and families, case management, millieu management, liason and counselling from prevention, promotion until psychiatric rehabilitation. Meanwhile the skill such as psycho-education, teaching, unit management, research and staff development can be added as their indirect roles.